DUKUNGAN KELUARGA PADA PASIEN DIABETES MELLITUS TIPE 2 DI KOTA SEMARANG - Arief Yanto; Dewi Setyawati (Universitas Muhammadiyah Semarang, 2017)
ntroduction: Diabetes mellitus is a chronic disease that is difficult to cure. This causes people with diabetes mellitus have psychological pressure. The family is one of the support systems for people with type 2 diabetes mellitus. This research aimed to know about family support of patients with type 2 diabetes mellitus.Method: The research is descriptive quantitative with cross sectional approach to know about family support in type 2 diabetes mellitus patients. The number of samples is 96 patients with type 2 diabetes mellitus at Regional Hospital KRMT Wongsonegoro Semarang.Results: The research showed that the family support of patients with type 2 diabetes mellitus had an average value of 61.52 with high level family support category of 70 respondents (72.9%) and low level family support category of 26 respondents (27.1%). Family support for patients who are married tends to be higher than single patients. Good family support will affect the implementation of the diabetes mellitus treatment program undertaken by the patient.Conclusion: Family support is an important factor in supporting the success of the type 2 diabetes mellitus treatment program. Therefore, nurses are expected to involve more families in providing nursing care to patients with type 2 diabetes mellitus.Keyword : Diabetes Mellitus, Family support